The Effect of Digital Tax Administration, Tax Literacy, and Taxpayer Awareness on Tax Compliance among Indonesian MSMEs - Rihan Mustafa Zahri; Ida Aryati Diyah Purnomo Wulan (Universitas Pekalongan, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) remains an important issue in Indonesia because the sector contributes significantly to national economic growth and tax revenue. The increasing adoption of digital taxation systems has created opportunities to improve compliance; however, taxpayers’ knowledge and awareness remain critical determinants of their compliance behavior. This study aims to examine the effects of digital tax administration, tax literacy, and taxpayer awareness on tax compliance among Indonesian MSMEs. A quantitative research design was employed using primary data collected through questionnaires distributed to MSME owners and managers who are registered taxpayers. The respondents were selected using purposive sampling techniques based on predetermined criteria. The collected data were analyzed using multiple regression analysis to assess the relationships among the research variables. The findings indicate that digital tax administration positively influences tax compliance by facilitating tax reporting, payment, and information access. Tax literacy also demonstrates a significant positive effect, suggesting that a better understanding of tax regulations encourages taxpayers to fulfill their obligations accurately and on time. In addition, taxpayer awareness has a positive impact on compliance, reflecting the importance of voluntary participation in supporting government revenue and national development. Simultaneously, digital tax administration, tax literacy, and taxpayer awareness significantly contribute to improving tax compliance among Indonesian MSMEs. These results provide practical implications for tax authorities in enhancing digital services and strengthening taxpayer education programs to foster higher compliance levels within the MSME sector.